Effect of trace silver on the conductivity and softening temperature of high conductivity and high heat resistance pure copper - Weiqiang Li; Haitao Liu; Zhenguo Hou; Zihao Zhang; Jincan Dong; Mengna Wang; Huiwen Guo; Kexing Song (Journal of Materials Research and Technology)
As a conductor material for high-power electronic devices, pure copper requires both conductivity and softening temperature. The effects of 0% (7N Cu), 0.015% (Ag150), 0.030% (Ag300), 0.045% (Ag450) and 0.059% (Ag590) Ag on the microstructure, conductivity and softening temperature of pure copper were studied. The results show that trace Ag can refine the microstructure of pure copper and improve the mechanical properties at room temperature and high temperature. The hardness values of 7N Cu, Ag150, Ag300, Ag450 and Ag590 were 112, 119.06, 122.14, 123.54 and 125.68HV, respectively, and the softening temperatures were 195, 310, 335, 344 and 345 °C, respectively. At the same time, the conductivity of the samples with different Ag content was more than 100.5 %IACS. The similar structure of Ag and Cu has little effect on the conductivity. On the one hand, the trace Ag element soluble in the matrix causes lattice distortion, inhibits recrystallization nucleation and grain boundary migration. On the other hand, the Ag element is polarized at the grain boundary, which reduces the grain boundary energy, decreases the atomic diffusion and increases the recrystallization temperature.